Use of Beauveria bassiana on the control of Tecla [Strymon megarus (Lepidoptera: Lycaenidae)] on pineapple (Ananas comosus (L.) Merr) - Rojas, Aníbal Rodríguez (2022)
Introduction. The increase in pineapple (Ananas comosus (L.) Merr.) production demands good quality fruits from the market, with less environmental impact and minimal use of chemical products. Objective. To determine the effective dose of the fungus Beauveria bassiana and the appropriate formulation as a bioinsecticide for the control of key (Strymon megarus Godart) in pineapple crop. Materials and methods. This research was developed from February to April 2019 on a farm at Río Jiménez, Guácimo, Limón, Costa Rica. An unrestricted randomized plot design with repeated means over time was established with seven treatments and five replicates per treatment. For each replicate, data from twenty-five pineapple fruits were collected weekly, from 50 to 92 days after floral induction (ddf). The treatments were: B. bassiana WP at doses of 1.0, 2.0, and 3.0 kg ha-1, two treatments of B. bassiana at 3 kg ha-1, Carrier adjuvant, and oil-miscible formulation (OL), there were also an absolute control without insecticide application, and a biological insecticide Turex 3.8 WP (Bacillus thuringiensis) at 1.0 kg ha-1. Five sprays were made per treatment, the first at 50 ddf, and the rest at seven-day intervals until reaching 78 days. Results. All treatments showed a lower incidence of old damage (gummosis) compared to the absolute control. Only the T7 (comercial control B. thurigiensis 1 kg ha-1) and T2 (B. bassiana a 1 kg ha-1) treatments showed a damage incidence lower than 5 % during the whole evaluation period without significant differences between them, but with the rest of the treatments. Conclusion. The T7 (commercial control B. thurigiensis 1 kg ha-1) and T2 (B. bassiana 1 kg ha-1), treatments were the most effective for the control of Strymon megarus Godart in pineapple crops.